Tibetan Plateau driven impact of Taklimakan dust on northern rainfall. (1st August 2020) - Liu, Yuzhi; Zhu, Qingzhe; Hua, Shan; Alam, Khan; Dai, Tie; Cheng, Yueming
Abstract: In our previous study (Li et al., 2019a), using observational data, we found some evidences of Taklimakan dust effects on the convective clouds over the Tibetan Plateau (TP) and then causing heavy rainfall in the downstream region. Here, a simulation study is performed to quantify the effects of Taklimakan dust on the cloud properties over the TP and downstream rainfall using the Spectral Radiation-Transport Model for Aerosol Species (SPRINTARS) coupled to the Nonhydrostatic Icosahedral Atmospheric Model (NICAM). The results indicate that the dusts in Taklimakan desert can be lifted to the northern slope of the TP. The dust aerosols transported to the TP can diminish the cloud effective radius (CER), but they can increase the cloud optical depth (COD), liquid water path (LWP) and ice water path (IWP) over the TP. The maximum impact of the dusts on the CER lags behind the peak of aerosol optical depth (AOD). Meanwhile, the dusts show a more profound impact on the ice-cloud optical depth (ICOD) than liquid-cloud optical depth (LCOD), which implies a more significant impact on the ice particles than liquid drops in convective clouds over the TP. Overall, due to the indirect effects of Taklimakan dust aerosols, the clouds are developed further over the TP. The eastward movement of the clouds polluted by Taklimakan dust can delay the occurrence of heavy rainfall for 12 h but intensify the rainfall over the northern area. This modeling study verified and quantified the indirect effect of Taklimakan dusts on the cloud properties over the TP and further impacts on the rainfall over the northern area. Highlights: Effects of Taklimakan dust on the cloud and rainfall surrounding the TP are simulated. Taklimakan dust can decrease the CER but increase the COD, LWP and IWP over the TP. Eastward movement of the dust-polluted clouds over the TP can intensify the rainfall over the northern area.